Domain wall motion control for racetrack memory applications - Kumar, Durgesh (2020)
Increasing demand for large capacity data storage can only be fulfilled by hard disk drives (HDDs) and to some extent by solid-state drives (SSDs). However, HDDs are favorable in many applications, as they are approximately 5-10 times cheaper than SSDs. Attempts are being made to increase the capacity of HDDs by technologies such as heat-assisted magnetic recording and microwave assisted magnetic recording. However, increasing the capacity has been a slow process and there are limitations in achieving areal density above 10 Tbpsi. Thus, the introduction of new technologies is important for attaining high capacity. In this scenario, domain wall (DW) memory is a potential candidate, but there are still many unsolved issues. One of these is ensuring controlled and reliable motion of DWs along the nanowire. In this paper, we provide an overview of existing technologies and our attempts to control DW motion. Many methods of fabricating pinning centers have been proposed and demonstrated. These methods can mainly be categorized as 1) geometrical and 2) non-geometrical methods. In the first part, we review the geometrical approach to pin DWs. Later, we provide an overview of our approaches to create pinning centers using non-geometrical means. Non-geometrical approach provides more advantages as it provides a variety of choices to tailor the properties. In particular, this approach suits scalability.